Increasing the Learning Result of Early Mathematics Odd and Even Numbers through Montessori "Cards and Counters" Activity: A Quasi-experimental Study - Darnis, Syefriani; Dodd, Jaime (Al-Athfal: Jurnal Pendidikan Anak, 2021)
Purpose – This study aims to obtain information about the effect of using the Montessori cards and counters’ mathematics activity on learning the result of odd and even numbers of 1 to 10 to the kindergarten students at the age of 4 to 5 years.Design/methods/approach – Quantitative research with a quasi-experimental model of non-equivalent control group design was carried out by applying conventional methods (lectures and giving questions by worksheets) to the control group and applying the Montessori learning model through the use of Cards and Counters apparatus in the experimental group with 30 samples of students, divided into two classes (control class and experiment class) at Kalyca Azzahra School, West Java, Indonesia.Findings – The result showed that students who used the Montessori Mathematics cards and counters achieved higher mathematics odd and even numbers are learning results than those who were not taught with the Montessori approach.Research implications/limitations – This research design used pre-test and post-test. Thus, the treatment results can be more accurate because they can be compared before and after treatment.Practical implications – The use of the Montessori apparatus becomes necessary in introducing early mathematics to children and attracting children’s attention to learn and facilitate teachers in teaching mathematics. Displaying the concrete objects as a medium will help teachers in teaching early mathematics to children. The cards and counters allow children to verify their understanding of the concept by matching the qualitative, concrete, quantitative, or abstract before slowly removing the concrete altogether.Originality/value – This research contributes to understanding learning strategies used in Early Mathematics, Odd and Even Numbers. The Montessori apparatus becomes more natural to understand it by the child’s cognitive development effortlessly. Paper type Research paper